Family Law in the United Nations 2030 Agenda - Meza Ingar, Carmen (2017)
The phenomenon of cultural globalization has also brought the concept of human rights to all corners of the earth. Thus, the development achieved by peoples thanks to technology could make possible human promotion bringing prosperity to many regions and, therefore, to all families, including the poorest. This is a concern of experts and politicians who have planned continental and world-wide efforts to overcome long-standing problems such as poverty, disease, and illiteracy. Although 2015, a date marked by the Millennium Goals, failed to achieve the proposed goals, it served to prepare the 2030 AGENDA, whereby States have renewed their commitments to make possible a new world for coming generations. We are confident that the new approaches, accompanied by realistic budgets, will make such goals possible.